2017
DOI: 10.1016/j.semcancer.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Cancer acidity: An ultimate frontier of tumor immune escape and a novel target of immunomodulation

Abstract: The link between cancer metabolism and immunosuppression, inflammation and immune escape has generated major interest in investigating the effects of low pH on tumor immunity. Indeed, microenvironmental acidity may differentially impact on diverse components of tumor immune surveillance, eventually contributing to immune escape and cancer progression. Although the molecular pathways underlying acidity-related immune dysfunctions are just emerging, initial evidence indicates that antitumor effectors such as T a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
373
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(398 citation statements)
references
References 171 publications
6
373
0
1
Order By: Relevance
“…Last, hypoxia along with tumour cell necrosis, increase the extracellular concentrations of the immune-inhibitory metabolites adenosine and lactate. 5255 The accumulation of lactate further leads to metabolic lactic acidosis (a low pH in the blood due to build up of lactic acid) and results in impaired cytotoxic T cell functions by interfering with T cell receptor (TCR)–triggered production of interferon-γ (IFNγ) 56 . These processes act together to inhibit effector immune cell maturation and promote T cell anergy and exhaustion (Fig 1).…”
Section: The Aberrant Tumour Vasculaturementioning
confidence: 99%
“…Last, hypoxia along with tumour cell necrosis, increase the extracellular concentrations of the immune-inhibitory metabolites adenosine and lactate. 5255 The accumulation of lactate further leads to metabolic lactic acidosis (a low pH in the blood due to build up of lactic acid) and results in impaired cytotoxic T cell functions by interfering with T cell receptor (TCR)–triggered production of interferon-γ (IFNγ) 56 . These processes act together to inhibit effector immune cell maturation and promote T cell anergy and exhaustion (Fig 1).…”
Section: The Aberrant Tumour Vasculaturementioning
confidence: 99%
“…The high abundance of lactate results in plastic remodeling of cytokinome and suppresses proliferation and mobility of cytotoxic T lymphocytes and NK cells, but supports formation of pro-tumorigenic TAMs and T regs [49,50]. Moreover, lactate may support T reg differentiation and survival in a MCT4-dependent manner [52,53]. Moreover, lactate may support T reg differentiation and survival in a MCT4-dependent manner [52,53].…”
Section: Metabolic Features Of Cancer Cells and Their Impacts On Infimentioning
confidence: 99%
“…In line with this, increased CO 2 production through the pentose phosphate pathway in cancer cells has been linked to an acidification of the tumor microenvironment (Kato et al, 2013). As broadly reviewed by Huber et al (2017), low pH negatively impacts the effector functions of both innate and adaptive immune cells. This was first described by Fischer et al, who demonstrated that low extracellular pH (pHe: 5.8) leads to decreased cytokine production and to a loss of cytotoxic effector functions without affecting cell viability (Fischer et al, 2000a,b; Muller et al, 2000).…”
Section: Waste Products Of Tumor Metabolism Affect Immunitymentioning
confidence: 99%
“…This was first described by Fischer et al, who demonstrated that low extracellular pH (pHe: 5.8) leads to decreased cytokine production and to a loss of cytotoxic effector functions without affecting cell viability (Fischer et al, 2000a,b; Muller et al, 2000). The effect of low pH on cytokine production by T cells correlated with impaired signaling pathways involving STAT5, ERK, AKT, p38 and NFAT (Huber et al, 2017). Importantly, buffering of low pH with bicarbonate therapy increased T-cell infiltration and impaired tumor growth.…”
Section: Waste Products Of Tumor Metabolism Affect Immunitymentioning
confidence: 99%